Curing kinetics of two commercial urea-formaldehyde adhesives studied by isoconversional method - Popović Mlađan; Budinski-Simendić Jaroslava; Jovičić Mirjana; Mursics Joszef; Điporović-Momčilović Milanka; Pavličević Jelena; Ristić Ivan (Hemijska Industrija, 2011)
Differential scanning calorimetry (DSC) was used to evaluate the curing kinetics of two commercial urea-formaldehyde (UF) adhesives having different formaldehyde to urea (F/U) ratio of 1.112 (UF1) and 1.086 (UF2). DSC measurements were done in dynamic scanning regime with heating rates of 5, 10, 15 and 20ºC•min-1 in order to determine the activation energy for each adhesive. Obtained data were analyzed using isoconversional methods with application of Ozawa-Flynn-Wall and Kissinger-Akahira-Sunose kinetic models. In addition, different catalyst levels were tested at the heating rate of 10°C/min. Results showed that the adhesive with higher F/U ratio achieved higher activation energy, while having lower peak temperature of curing reaction. It was also noticed that the increase of catalyst level influenced the increase of reaction enthalpy of the adhesive with lower F/U ratio.